In Vitro Antioxidant and Anti-Obesity Activities of Ethanolic Extract from Microalgae Strain MRB-2 - Dwi Ni’maturrohmah; Cici Darsih; Hani Susanti; Noor Hidhayati; Anastasia Wheni Indrianingsih; Sri Handayani; Rizal Maulana Hasby; Marlyn Dian Laksitorini (UIN Sunan Gunung Djati Bandung, 2024)
Obesity has a 15-fold higher risk of coronary heart disease, stroke, and diabetes mellitus. Microalga isone of the natural resources that potentially treat obesity. The purpose of this study was to evaluate the total phenolic contents (TPC), antioxidant, and anti-obesity properties of ethanolic extract of microalgae strain MRB-2. The TPC was determined using the Follin-Ciocalteu method. The antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, and the anti-obesity was analyzed using an anti-lipase pancreatic assay. The morphology of microalga cells was also determined using Scanning Electron Microscopy (SEM). The results revealed that the TPC of ethanolic extract from the ultrasound extraction method was higher than the maceration method with the value of 2.75±0.26 mg GAE/g. While the scavenging activity toward DPPH radicals of ethanolic extract from the maceration method was higher than ultrasound, with a value of 38.92±1.94% at 0.8 mg/mL. The lipase inhibitory activity of extract from the maceration method was higher than ultrasound with a value of 20.81±2.24% at 0.38 mg/mL. Our results indicate that ethanolic extract of MRB-2 was potentially developed for anti-obesity foods and health-functional foods derived from new peatland microalgae.